The Relevance of Ibn Rushd's Thought in the Revitalization of the Modern Islamic Boarding School Education System - Purnomo, Purnomo; Sa’adi, Sa’adi; Nugroho, Muhammad Aji (Journal of Instructional and Development Researches, 2025)
his article presents an in-depth argument regarding implementing Ibn Rushd's philosophical thought as a systematic and authentic intellectual framework to address the challenge of aligning the classical Islamic scientific heritage with the times' demands prioritizing rationality, science, and critical thinking. Ibn Rushd's philosophy, which is fundamentally centered on the thesis of absolute harmonization and the unity of truth between reason (burhan) and revelation (sharia), offers a solid epistemological and theological foundation for the holistic integration of general and religious sciences. This research method is a content analysis of authoritative secondary sources on Ibn Rushd's thought relevant to the philosophy of education. This article outlines four pillars of implementation in detail. First, the design of an integrated curriculum based on the principle of the unity of truth rejects the dichotomy of knowledge. It utilizes the method of allegorical interpretation (ta'wil) in a controlled manner for experts. Second, the application of differentiated pedagogy inspired by the classification of three levels of human ability (rhetorical, dialectical, and demonstrative) allows for the maximum and progressive development of the potential of each student. Third, ethics education should be strengthened through an imaginative-narrative approach to form what is analogous to the "essential minimum of character" (Minima Naturalia), a concept of irreducible moral integrity. Fourth, the conceptualization of kiai leadership as a "Philosopher-King" figure who combines intellectual depth, moral nobility, and active social involvement.